Use of Nanoparticles As Contrast Agents for the Functional and Molecular Imaging of Abdominal Aortic Aneurysm - Emeto, Theophilus I.; Alele, Faith O.; Smith, Amy M.; Smith, Felicity M.; Dougan, Tammy; Golledge, Jonathan (Frontiers in Cardiovascular Medicine, 2017)
Abdominal aortic aneurysm (AAA) is a degenerative disease of the aorta common in adults older than 65 years of age. AAA is usually imaged using ultrasound or computed tomography. Molecular imaging technologies employing nanoparticles have been proposed as novel ways to quantify pathological processes, such as inflammation, within AAAs as a means to identify the risk of rapid progression or rupture. This article reviews the current evidence supporting the role of nanoparticle-based imaging in the management of AAA. Currently, ultrasmall superparamagnetic nanoparticles enhanced magnetic resonance imaging appears to hold the greatest potential for imaging macrophage-mediated inflammation in human AAA.